2018
DOI: 10.1080/09168451.2018.1514249
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-β-cyclodextrin potentiates the BITC-induced anti-cancer effect through modulation of the Akt phosphorylation in human colorectal cancer cells

Abstract: Methyl-β-cyclodextrin (MβCD) is an effective agent for the removal of plasma membrane cholesterol. In this study, we investigated the modulating effects of MβCD on the antiproliferation induced by benzyl isothiocyanate (BITC), an ITC compound mainly derived from papaya seeds. We confirmed that MβCD dose-dependently increased the cholesterol level in the medium, possibly through its removal from the plasma membrane of human colorectal cancer cells. The pretreatment with a non-toxic concentration (2.5 mM) of MβC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…All of the mice treated with methylated cyclodextrin or doxorubicin died within 70 days, whilst all the mice treated with the folate-derivative survived for at least 140 days. In other work, the simpler methylated cyclodextrin was shown to remove cholesterol from plasma membranes, and, in conjunction with benzyl isothiocyanate, it demonstrated enhanced cytotoxicity against human colorectal cancer cells [80]. Similar effects could be obtained using methylated cyclodextrin along with the anticancer drug tamoxifen; the In other work, the simpler methylated cyclodextrin was shown to remove cholesterol from plasma membranes, and, in conjunction with benzyl isothiocyanate, it demonstrated enhanced cytotoxicity against human colorectal cancer cells [80].…”
Section: Medical Applicationsmentioning
confidence: 76%
“…All of the mice treated with methylated cyclodextrin or doxorubicin died within 70 days, whilst all the mice treated with the folate-derivative survived for at least 140 days. In other work, the simpler methylated cyclodextrin was shown to remove cholesterol from plasma membranes, and, in conjunction with benzyl isothiocyanate, it demonstrated enhanced cytotoxicity against human colorectal cancer cells [80]. Similar effects could be obtained using methylated cyclodextrin along with the anticancer drug tamoxifen; the In other work, the simpler methylated cyclodextrin was shown to remove cholesterol from plasma membranes, and, in conjunction with benzyl isothiocyanate, it demonstrated enhanced cytotoxicity against human colorectal cancer cells [80].…”
Section: Medical Applicationsmentioning
confidence: 76%
“…This further supported its potential for the control and suppression of microbial pathogens in food. It has been reported that BITC can regulate the expression and function of apoptosis-related proteins through c-Jun N-terminal kinase, extracellular signal-regulated kinase, and p38 signal transduction pathways, leading to tumor cell apoptosis . However, these pathways are conserved in eukaryotic cells, and it is hard to connect them to the bactericidal effects of BITC on S.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BITC can regulate the expression and function of apoptosis-related proteins through c-Jun N-terminal kinase, extracellular signal-regulated kinase, and p38 signal transduction pathways, leading to tumor cell apoptosis. 21 However, these pathways are conserved in eukaryotic cells, and it is hard to connect them to the bactericidal effects of BITC on S. aureus cells. In most cases, the antibacterial activity of BITCs was attributed to its destructive roles in cell envelope integrity, involving Clostridium perfringens, S. aureus, etc.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition, they increase apoptosis-related proteins due to activation of p53-family genes, while decreasing metastasis-related proteins. Because of all these reasons, BITC, PEITC and sulforaphane were capable of ameliorating the inflammation associated with colon cancer ( 116 , 167 ). In HT29 colon cancer cells, BITC and PEITC have been demonstrated to have anti-metastatic and anti-inflammatory effects against colon cancer, and it slowed the migration of colon cancer cells through the activation of p53 pathway ( 147 , 168 , 169 ).…”
Section: Functional Ingredients As Therapeutics Against Gastrointesti...mentioning
confidence: 99%